Fluid Functionality: an Examination of Shifting Identities Using North American Indian German Silver Brooches at the Milwaukee Public Museum as a Case Study - (:unkn) unknown (My University, 2018)
This thesis explores the social lives of Woodland silver and German silver brooches beginning in the late 18th century up to the present day using examples from the collections at the Milwaukee Public Museum. As a popular trade item introduced by Europeans, silver brooches provided a new medium for personal adornment in North American indigenous communities throughout the Woodland region. Brooches were fastened on clothing as singular items and occasionally worn in the hundreds to display wealth, status, and other aspects of identity. The majority of brooches used for this project originate from Canada, New York, and Wisconsin. Also included are brooches collected from Mexico and contemporary examples from Rhode Island. A biographical approach is adopted in order to consider the social lives of Woodland German silver brooches. This project relies on Alfred Gell’s (1998) concept of the secondary agency of material culture in order to investigate how brooches functioned as social actors throughout the course of their life trajectories. The social function of brooches, from active trading partners in the Fur Trade to their transition into hybrid identities intended to mediate social landscapes, is elaborated and explored. Additionally, how brooches functioned from the mid-19th century through the museum age of collecting and the re-emergence of indigenous silversmithing is discussed. Evidence is provided to argue that when worn, brooches were used by primary human actors as vehicles to assert aspects of individual and collective identities in order to influence the social contexts in which they operated in.
Keywords: German Silver; Museum Collecting; Object biographies; Personal Adornment